(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
This article presents a characterization of evangelical woman and young associations in Colombia along the first middle of twentieth century, which served like a fundamental strategy of this religious option for get a space in the public national sphere and get a position from traditional heralds of hegemonic power, also for extend their ideas among the population. Through of “sociability” category aims to elucidate the grade of evangelical incidence during the period and the way in which their religious agendas got to permeating or been permeated by others social camps like culture and politics.